Normal Values of Real-Time 3-Dimensional Echocardiographic Parameters in a Healthy Japanese Population: The JAMP-3D Study - Yamamoto, Kazuhiro; Iwakura, Katsuomi; Watanabe, Hiroyuki; Yoshikawa, Junichi; Abe, Yukio; Murata, Kazuya; Hirata, Kumiko; Yamada, Satoshi; Nishigami, Kazuhiro; Nakatani, Satoshi; Fukuda, Shota; Negishi, Kazuaki; et al. (Circulation Journal, 2012)
Background: The recently developed real-time 3-dimensional echocardiography (RT3DE) is a promising imaging method to quantify cardiac chamber volumes and their functions in clinical practice. However, normal reference values of RT3DE parameters have not been fully investigated in a large, healthy Japanese population. Methods and Results: This study consisted of 410 healthy subjects aged from 20 to 69 years who had a RT3DE at one of the 23 collaborating institutions. All subjects had no history of cardiac disease and no risk factors. The mean values in men and women were as follows: 50±12ml/m2 and 46±9ml/m2 for left ventricular (LV) end-diastolic volume index, 19±5ml/m2 and 17±4ml/m2 for end-systolic volume index, 61±4% and 63±4% for ejection fraction, 64±12g/m2 and 56±11g/m2 for mass index, 23±6ml/m2 and 24±6ml/m2 for left atrial (LA) maximum volume index, 10±3ml/m2 and 10±3ml/m2 for minimum volume index, and 58±6% and 58±6% for percent volume change. LV sizes decreased with age, whereas LV mass index did not change. LA sizes slightly increased with age. Conclusions: This multicenter investigation determined normal reference values for LV and LA sizes, and their functional parameters on RT3DE in a large, healthy Japanese population. The results of the present study support the use of RT3DE for the diagnosis and management of cardiovascular disease. (Circ J 2012; 76: 1177-1181)